Impactos da financeirização sobre a fragilidade micro e macroeconômica: um estudo para a economia brasileira entre os anos de 1995-2012 - Bernardo Padua Jardim de Miranda (2013)
This thesis aims to analyze the impact of Brazilian economy financialization over the non-financial open capital companies in the period from 1995 to 2012, as well as its effects on these companies and economy fragility. We adopted the concept proposed by the French regulationists, in which financialization means a new pattern of accumulation, in which productive activities are subordinated to finance. In this process, there is a search for short-term results at the expense of long-term, compromising the companies and economy performance. The first chapter presents a theoretical discussion about the financialization concept and process, and combines the post-Keynesian and regulationist theories to analyze the financialization effects over micro and macroeconomic fragility. Chapter two shows how the macroeconomic and institutional environments conditioned the financialization process emergence in the Brazilian economy in 1980 and its intensification in the 1990 and 2000 decades, as well as its effects over non-financial open companies. For that purpose economic and financial data, available in the accounting reports of these companies from 1995 to 2008, were analyzed and related to the financialization process. The third chapter examines the non-financial open capital companies in New Market (NM) and Level 2 ( N2), using the ownership and control structure and the governance mechanisms to investigate their adoption of shareholders value, since the alignment to this governance form is the microeconomic side of this new accumulation process, in which productive decisions are subordinated to financial capital return. Our results showed an increase in the wealth distribution to shareholders over the period, as well as the adoption of managerial practices to enlarge this wealth. The increase in wealth distribution to shareholders caused the retention rate to drop, and has had negative effects on the asset formation of these companies and of the economy. These facts suggest that these companies have increased the search for short-term results at the expense of long-term, and that there is a convergence to the Anglo-Saxon model of corporate governance, which shows that there is a dominance of the reinter logic accumulation process over these companies. However, this process has its own characteristics determined by the macro and micro institutional Brazilian economy specificities, which differentiates it from the financialization observed in developed countries. We also observed that the search for short-term results and the convergence to the shareholders value, presented in the Brazilian economy financialization, increased these companies and economy fragility, as these companies increased the debt in its capital structure without the clear intent to apply this resource in productive activity.